Early hemi-diaphragmatic plication through a video assisted minithoracotomy in postcardiotomy phrenic nerve paresis - Tsakiridis, Kosmas; Visouli, Aikaterini N.; Zarogoulidis, Paul; Machairiotis, Nikolaos; Christofis, Christos; Stylianaki, Aikaterini; Katsikogiannis, Nikolaos; Mpakas, Andreas; Courcoutsakis, Nicolaos; Zarogoulidis, Konstantinos (Journal of Thoracic Disease; Vol 4, Supplement 1 (November 11, 2012): Journal of Thoracic Disease, 2012)
New symptom onset of respiratory distress without other cause, and new hemi-diaphragmatic elevation on chest radiography postcardiotomy, are usually adequate for the diagnosis of phrenic nerve paresis. The symptom severity varies (asymptomatic state to severe respiratory failure) depending on the degree of the lesion (paresis vs. paralysis), the laterality (unilateral or bilateral), the age, and the co-morbidity (respiratory, cardiac disease, morbid obesity, etc). Surgical treatment (hemi-diaphragmatic plication) is indicated only in the presence of symptoms. The established surgical treatment is plication of the affected hemidiaphragm which is generally considered safe and effective. Several techniques and approaches are employed for diaphragmatic plication (thoracotomy, video-assisted thoracoscopic surgery, video-assisted mini-thoracotomy, laparoscopic surgery). The timing of surgery depends on the severity and the progression of symptoms. In infants and young children with postcardiotomy phrenic nerve paresis the clinical status is usually severe (failure to wean from mechanical ventilation), and early plication is indicated. Adults with postcardiotomy phrenic nerve paresis usually suffer from chronic dyspnoea, and, in the absence of respiratory distress, conservative treatment is recommended for 6 months -2 years, since improvement is often observed. Nevertheless, earlier surgical treatment may be indicated in non-resolving respiratory failure. We present early (25th day postcardiotomy) right hemi-diaphragm plication, through a video assisted mini-thoracotomy in a high risk patient with postcardiotomy phrenic nerve paresis and respiratory distress. Early surgery with minimal surgical trauma, short operative time, minimal blood loss and postoperative pain, led to fast rehabilitation and avoidance of prolonged hospitalization complications. The relevant literature is discussed.